Fecal Diversion in Complex Perianal Fistulizing Crohn's Disease - Yamamoto, Takayuki; Shimoyama, Takahiro (Clinics in Colon and Rectal Surgery, 2022)
Complex perianal Crohn's disease (CD) remains a challenging problem. Fecal stream is thought to be a trigger of disease progression in patients with CD. In patients with refractory perianal CD, diversion of fecal stream is sometimes required to alleviate clinical symptoms when medical and local surgical management are unsuccessful. Several studies evaluated the outcomes of fecal diversion for complex perianal CD. After fecal diversion, the majority of patients achieved early clinical response, but the prospect of restoring bowel continuity was low (approximately 20%). Nearly half of the patients eventually required proctectomy. A number of studies attempted to identify predictive factors for the outcomes of fecal diversion. Only rectal involvement was associated with unsuccessful restoration of bowel continuity. Biologic therapy did not seem to improve the efficacy of fecal diversion, although the evidence level was low because of insufficient data or methodological limitations. Based on these results, fecal diversion may be useful in alleviating clinical symptoms related to severe perianal CD and avoiding immediate proctectomy. The impact of biologic therapy on the outcomes of fecal diversion should be further investigated.
Keywords: Crohn's disease; perianal Crohn's disease; fecal diversion; proctectomy; biologic therapy